New targets for old drugs: cardiac glycosides inhibit atrial-specific K2P3.1 (TASK-1) channels - Schmidt, Constanze; Wiedmann, Felix Tobias; Gaubatz, Anne-Rike; Ratte, Antonius; Katus, Hugo; Thomas, Dierk (The journal of pharmacology and experimental therapeutics, 2018)
Cardiac glycosides have been used in the treatment of arrhythmias for more than 200 years. Two-pore-domain (K2P) potassium channels regulate cardiac action potential repolarization. Recently, K2P3.1 [tandem of P domains in a weak inward rectifying K+ channel (TWIK)-related acid-sensitive K+ channel (TASK)-1] has been implicated in atrial fibrillation pathophysiology and was suggested as an atrial-selective antiarrhythmic drug target. We hypothesized that blockade of cardiac K2P channels contributes to the mechanism of action of digitoxin and digoxin. All functional human K2P channels were screened for interactions with cardiac glycosides. Human K2P channel subunits were expressed in Xenopus laevis oocytes, and voltage clamp electrophysiology was used to record K+ currents. Digitoxin significantly inhibited K2P3.1 and K2P16.1 channels. By contrast, digoxin displayed isolated inhibitory effects on K2P3.1. K2P3.1 outward currents were reduced by 80% (digitoxin, 1 Hz) and 78% (digoxin, 1 Hz). Digitoxin inhibited K2P3.1 currents with an IC50 value of 7.4 µM. Outward rectification properties of the channel were not affected. Mutagenesis studies revealed that amino acid residues located at the cytoplasmic site of the K2P3.1 channel pore form parts of a molecular binding site for cardiac glycosides. In conclusion, cardiac glycosides target human K2P channels. The antiarrhythmic significance of repolarizing atrial K2P3.1 current block by digoxin and digitoxin requires validation in translational and clinical studies.
Gesehen am 30.03.2020